TRAVEL STRESS AND STRESS-COPING STRATEGIES ADAPTED BY INTERNATIONAL TOURISTS AND TRAVEL ORGANIZATION’S AWARENESS IN BANGKOK - Mathur, Piyush; Batra, Adarsh (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
As the Tourism is increasing globally with the rise in number of International tourists every year where travelling has become an inseparable part of lifestyle but the fact cannot be ignored that it may actually cause stress, and rise in anxiety and tension at different phases of travel which may cause negative experience among International tourists. Thus, this study will contribute to the knowledge of source of travel stress, destination factors and how tourists coming to Bangkok manage and reduce it. As the awareness about the travel-related stress is still less so it is necessary to know what the role of travel organizations is in dealing with tourist’s stress problems in Bangkok. Qualitative research method is used for the collection of data and in-depth, semi-structured interviews were conducted during 28th February 2020 to 6th March 2020 with 10 International tourists and 2 travel organizations in Bangkok and for the data analysis constant comparison method was used. Results indicate that travel-related stress arises at the initial stage, which is pre-trip phase, continues with during trip phase, at destination and ends with post trip phase. The stress coping methods adapted by International tourists are social support, relaxation, entertainment, meditation, management of trip, and destination activities such as enjoying nightlife in Bangkok. Also, this study reveals that travel organizations provide destination knowledge, safety measures, travel alternatives, guidelines to staff, address complaints, offer compensation, to help tourist prevent from stressful situation in Bangkok. Keywords: Travel Stress, Stress coping, International Tourist, Travel organization, Bangkok